THE ROLE OF CORRECTIVE FEEDBACK ON ACADEMIC WRITING PERFORMANCE: EFL STUDENTS’ PERCEPTIONS - Sri Wahyuningsih (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2020)
In the context of higher education, corrective feedback plays a crucial part in academic writing. This paper, therefore, aims to explore the role of corrective feedback on the academic writing performance of EFL students at State Islamic Institute of Kudus. The study employed a qualitative research. In order to gather data, the writer interviewed the students about the perception of the use corrective feedback in enhancing their performance in academic writing. In addition, observation and documentation were conducted to get detail information. The result showed that corrective feedback including the aspects of providing and receiving feedback has led to better improvement in students’ academic writing performance. Indeed, they become more confident in performing their academic writing task. Further, through corrective feedback, students are highly pursued to give more comments regarding the performance of their peers in academic writing. In addition, lecturers merely give clarifications towards the corrective feedbacks in academic writing class by provoking question and answer to promote the students’ critical thinking skills.